2013
DOI: 10.1111/1745-9125.12024
|View full text |Cite
|
Sign up to set email alerts
|

The Unintended Consequences of Being Stopped or Arrested: An Exploration of the Labeling Mechanisms Through Which Police Contact Leads to Subsequent Delinquency

Abstract: Much debate has taken place regarding the merits of aggressive policing strategies such as “stop, question, and frisk.” Labeling theory suggests that police contact may actually increase delinquency because youth who are stopped or arrested are excluded from conventional opportunities, adopt a deviant identity, and spend time with delinquent peers. But, few studies have examined the mechanisms through which police contact potentially enhances offending. The current study uses four waves of longitudinal data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 61 publications
8
139
1
1
Order By: Relevance
“…This allows for a more theoretically relevant analysis, as the indirect effect of arrest through delinquent peers, for instance, is influenced by the inclusion of the indirect effect through prosocial peer exclusion. Labeling theory and its extensions indicate that the direct effect of justice system involvement on delinquency should disappear once the mechanisms that account for increased delinquency are taken into account (e.g., see [7,60]); yet prior research has shown that a direct effect between justice system contact and delinquency remains even after accounting for indirect effects [40,78]. Therefore, a direct effect between arrest and delinquency is included to capture any effects not accounted for by the mediators.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This allows for a more theoretically relevant analysis, as the indirect effect of arrest through delinquent peers, for instance, is influenced by the inclusion of the indirect effect through prosocial peer exclusion. Labeling theory and its extensions indicate that the direct effect of justice system involvement on delinquency should disappear once the mechanisms that account for increased delinquency are taken into account (e.g., see [7,60]); yet prior research has shown that a direct effect between justice system contact and delinquency remains even after accounting for indirect effects [40,78]. Therefore, a direct effect between arrest and delinquency is included to capture any effects not accounted for by the mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has highlighted the central role of deviant group involvement in the labeling process [9,40,78] but few studies have examined how the relationship between justice system involvement and delinquent groups varies during adolescence.…”
Section: Involvement With Delinquent Groupsmentioning
confidence: 99%
See 3 more Smart Citations